Suitability analysis of solar photovoltaic farms - Rodrigues, Sara (2017)
Rodrigues, S., Coelho, M. B., & Cabral, P. (2017). Suitability analysis of solar photovoltaic farms: A Portuguese case study. International Journal of Renewable Energy Research (IJRER), 7(1), 244-254.